2016
DOI: 10.1590/s1808-185120161501154498
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Lumbar Hernias by Endoscopic Nucleoplasty With Radiofrequency

Abstract: Objective: To evaluate the postoperative outcomes of minimally invasive technique for treating lumbar disc herniation in patients undergoing percutaneous endoscopic nucleoplasty with radiofrequency in the center of minimally invasive procedures Veracruz (CEMIVER) of the HRAEV.. Methods: A descriptive, comparative, ambispective and longitudinal study. The clinical records of patients who underwent herniated disc surgery were reviewed from March 2010 to March 2015. Inclusion criteria were individuals of both sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…O número de pessoas com doenças crônicas na coluna tem se acentuado no Brasil, chegando a cerca de 18,5% da população adulta segundo a Pesquisa Nacional de Saúde de 2013 [1]. O tratamento conservador para dores crônicas na coluna são relacionados com reprogramação postural ou medicamentos para dor, porém quando estes não são su cientes para que o paciente tenha uma boa qualidade de vida, pode ser recomendado o processo cirúrgico [2]. Em diversos casos a cirurgia na coluna vertebral utiliza implantes metálicos para o tratamento, como as hastes pediculares posteriores.…”
Section: Introductionunclassified
“…O número de pessoas com doenças crônicas na coluna tem se acentuado no Brasil, chegando a cerca de 18,5% da população adulta segundo a Pesquisa Nacional de Saúde de 2013 [1]. O tratamento conservador para dores crônicas na coluna são relacionados com reprogramação postural ou medicamentos para dor, porém quando estes não são su cientes para que o paciente tenha uma boa qualidade de vida, pode ser recomendado o processo cirúrgico [2]. Em diversos casos a cirurgia na coluna vertebral utiliza implantes metálicos para o tratamento, como as hastes pediculares posteriores.…”
Section: Introductionunclassified
“…3,5,6 Despite the fact that less invasive techniques have a long learning curve, higher cost, and longer surgical time, this treatment is the trend and literature data have shown that this method is safe, and its indication is increasing in as the technique gains acceptance. 3,[6][7][8][9][10] Minimally invasive spinal surgery has gradually evolved, endoscopic equipment being improved and demonstrating progressive success and, currently, two percutaneous decompression techniques are the most used: transforaminal, described in 2004 by Tsou and Yeung, and interlaminar, described by Choi in 2005. 7 The advantages of using minimally invasive techniques are a smaller surgical incision and less aggression of the soft tissues (multifidus muscles, ligaments, and the facet joint capsules).…”
Section: Introductionmentioning
confidence: 99%